Integrasi Model Kesuksesan Adopsi E-Commerce Berbasis Technological Frames of References (TFR) – Knowledge Management (KM) - Faradillah Faradillah; Imelda Saluza; Muhammad Fadhiel Alie; Andini Utari Putri (UNIVERSITAS INDO GLOBAL MANDIRI, 2022)
This study aims to examine several variables supporting the implementation of e-Commerce websites as digital platforms in supporting the business activities of SMEs. Several previous studies have found several variables/factors that support the implementation of e-Commerce with each perspective raised, so that in this study the variables/factors raised are the extraction of all factors from various perspectives and are expected to accommodate different points of view and previous research. Factor extraction is carried out using the Principal Component Analysis (PCA) method using the SPSS 22 Version tool to identify variables/factors from various and various needs, several factors that have components will be extracted and viewed in one category so as to minimize ambiguity factors as e-Commerce Enablers. In this study, data were collected through interviews and online dissemination to Clothing Line Business Actors and staff using digital platform users as many as 75 respondents and obtained some supporting data related to the use of digital platforms in the application of e-Commerce in daily business. Based on the extraction results obtained 5 main drivers that become e-Commerce Enabler based on several models of e-Commerce implementation based on Technological Frames of References (TFR) and Knowledge Management, namely: Organizational Trigger (OT), Environmental Trigger (ET), Individual Intention (II) , Knowledge Aspect and Capability (KAC), and Technology Infrastructure (IT) with each factor with components extracted so as to minimize ambiguity and still accommodate various needs and perspectives.Keywords : Specification Design, Information System, Integrated Document, Rational Unified Process, MASS Cargo